142 Relapse frequency and depression ratings in a community sample of relapsing multiple sclerosis patients. Issue 3 (9th February 2012) - Moore, P; Clarkson, H; Baker, K E; Luppe, S; Robertson, N P
Abstract : Background: Relatively little is known about the effect of MS relapses on mood. While it has been speculated that relapses may act as a reminder of the chronic nature of the disease and cause restrictions in social and occupational activities, the impact of relapse frequency on mood is currently unresearched. Methods: Reports of number of MS relapses in the preceding 12 months along with current depression scores from the Hospital Anxiety and Depression Scale (HADS) were gathered from a community sample of 95 participants with a relapsing form of MS. Results: The mean number of relapses reported as occurring over the previous 12 months was 0.83 (SD 0.95, range 0–4). Current mean HADS depression scores were 5.66 (SD 5.84, range 0–20) and 35.8% of patients met criteria for possible caseness of depression. There was a significant linear relationship between HADS depression scores and number of relapses (F=9.42 (df 1.93) p<0.01) that explained 8.2% of the variance in depression scores. Conclusions: Individuals with higher rates of disease activity in the form of acute symptom exacerbations may have poorer outcomes in terms of mood difficulties. This relationship has implications when considering the potential benefits of disease modifying treatments and when identifying individuals who may benefit from psychiatric or psychological intervention.